PRODUCTION COMPARISON OF PURSE SEINE CATCHES LANDED AT PPS NIZAM ZACHMAN JAKARTA - Maulidina, Melly; Apriliani, Izza Mahdiana; Suryana, Asep Agus Handaka; Dewanti, Lantun Paradhita (Universitas Mataram, 2025)
The Ministry of Fisheries and Fisheries (KKP) issued the latest policy in the form of Measured Fishing (PIT) to maintain the sustainability of natural resources. PPS Nizam Zachman is one of the fishing ports that implements this policy by providing weighbridge facilities. Weighbridges are useful in recording the production of landed catches. One of the highest productions at PPS Nizam Zachman is purse seine. Therefore, this study aims to analyze the comparison of purse seine production weighed using a dock scale with a weighbridge. The method used in this study is in the form of a survey. This study uses primary data obtained through interviews, as well as secondary data obtained through the annual report of PPS Nizam Zachman. This study uses descriptive and comparative descriptive analysis. The results of this study are the average production of purse seine catch from pier weighers of 3,546,809.30 kg and weighbridges of 3,761,069.60 kg, and an average difference of 214,260.30 kg. The comparison of the two is seen with the T-Test which produces a P Value of < 0.05, meaning that there is a significant difference. The average accuracy level of weighbridges of 94.31% shows that the data produced is not accurate, due to several factors such as the use of blong, the availability of vehicle fuel, and the difference in fish transport drivers.